Electrophoretic Analysis of Indian Isolates of Mycoplasma agalactiae and Mycoplasma bovis by SDS-PAGE and Immunoblotting - Amit Kumar; N. C. Srivastava; V. P. Singh; Jai Sunder (Veterinary Medicine International)
Mycoplasma agalactiae and Mycoplasma bovis both are responsible for respiratory conditions in sheep and goats. M. agalactiae is a major pathogen of sheep and goats and accounts for almost 90% of outbreaks of contagious agalactia syndrome in goats and almost 100% in sheep. On the basis of clinical signs and cultural, morphological, and biochemical characterization it is almost impossible to differentiate between both the species. Moreover, due to presence of genomic and proteomic similarity most of the time routine diagnostic tests fail to differentiate between them. Hence the present study was conducted to find out the protein profile of isolates of both the species by SDS-PAGE and to find out the cross-reacting as well as differentiating immunogenic proteins by Immunoblotting, which can be of immunoprophylactic as well as diagnostic values. The study revealed 6-7 major immunogenic cross-reactive proteins with the presence of two important non-cross-reacting species specific polypeptides particularly 25.50 and 24.54 kDa in M. agalactiae and M. bovis, respectively, that might be of diagnostic values.